2017
DOI: 10.1111/iej.12788
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of XP‐endo Finisher and XP‐endo Finisher R in removing root filling remnants: a micro‐CT study

Abstract: Silva EJNL, Belladonna FG, Zuolo AS, Rodrigues E, Ehrhardt IC, Souza EM, De-Deus G. Effectiveness of XP-endo Finisher and XP-endo Finisher R in removing root filling remnants: a micro-CT study. International Endodontic Journal, 51, 86-91, 2018. Aim To evaluate the efficacy of filling material removal from oval-shaped canals after the use of supplementary files (XP-endo Finisher and XP-endo Finisher R) through microcomputed tomographic (micro-CT) analysis. Methodology The root canals of twenty maxillary sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
111
2
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(134 citation statements)
references
References 30 publications
9
111
2
12
Order By: Relevance
“…This reduction was, however, lower than that reported in a previous study (60%) (Silva et al . ) with the difference probably being related to the more complex anatomy of the isthmus‐containing roots used in the present study. Once again, the use of the solvent with the XP‐endo Finisher R did not significantly affect filling material removal from the apical third of the root canal system.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This reduction was, however, lower than that reported in a previous study (60%) (Silva et al . ) with the difference probably being related to the more complex anatomy of the isthmus‐containing roots used in the present study. Once again, the use of the solvent with the XP‐endo Finisher R did not significantly affect filling material removal from the apical third of the root canal system.…”
Section: Discussionmentioning
confidence: 76%
“…Early reports have revealed a significant reduction of gutta‐percha remnants when the XP‐endo Finisher R was used in the retreatment of single‐rooted teeth (Silva et al . ). Considering its lateral action, it is hypothesized that this instrument could improve filling material removal from the isthmus area.…”
Section: Introductionmentioning
confidence: 97%
“…Taken together, these findings are in line with a study that reported that XP‐endo Finisher and XP‐endo Finisher R instruments were equally effective in removing filling remnants (Silva et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…The only study published so far evaluating the use of XP‐endo Finisher R during retreatment reported that it was effective in removing residual filling material from oval‐shaped canals and had comparable results to its counterpart used for treatment (XP‐endo Finisher) (Silva et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…This greater effectiveness of the XP‐endo ® Finisher is in agreement with other studies (Elnaghy et al , Keskin et al ). The change in the alloy pattern over the last 10 mm causes the instrument to touch the walls of the canals and IRR cavities without wear and debris formation (Turkaydin et al , Uygun et al , Silva et al ). The superior results of the EDDY ® group compared with the EndoActivator ® group may be due to their greater cavitation effect (Conde et al , Urban et al ).…”
Section: Discussionmentioning
confidence: 99%